CASTING OF DETAILS OF WEAR-RESISTANT CHROME CAST IRONS FOR CHROMIC MILLS IN COMBINED MOLDS AND CHILLS - K. E. Baranovskij; V. M. Iljushenko; Ju. L. Stanulenis (Литьë и металлургия)
Relative wear resistance of chrome cast irons of eutectic composition is determined in laboratory and industry conditions. Complex alloyed eutectic cast iron with increased wear resistance and mechanical characteristics is developed.